2016
DOI: 10.1007/s12630-016-0704-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravenous lidocaine on the transcerebral inflammatory response during cardiac surgery: a randomized-controlled trial

Abstract: Purpose Postoperative cognitive dysfunction (POCD) occurs frequently after cardiac surgery. The pathophysiology of POCD remains elusive, but previous work showed that intravenous lidocaine may be protective against POCD, possibly by modulating cerebral inflammation. We hypothesized that intravenous lidocaine would attenuate the cerebral inflammatory response to cardiopulmonary bypass (CPB) by reducing the transcerebral activation gradients of platelets, leukocytes, and/or platelet-leukocyte conjugates. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…39,40 In models of tissue injury, lidocaine has been shown to prevent leukocyte accumulation and endothelial adherence along with consequent microvascular thrombus when applied preventatively and to restore microvascular blood flood by disadhering leukocytes from the endothelium when applied postinjury. 41,42 As part of this study and reported elsewhere, 43 paired jugular venous and arterial samples were drawn on the first 202 randomized patients to measure transcerebral gradients of activated platelets and platelet-leukocyte conjugates. In that cohort, we observed a significant reduction in the transcerebral activation of platelet-monocyte conjugates after aortic cross-clamp release in patients who received lidocaine, which we hypothesized might reflect reduced cerebral inflammation during CPB.…”
Section: Perioperative Medicinementioning
confidence: 99%
“…39,40 In models of tissue injury, lidocaine has been shown to prevent leukocyte accumulation and endothelial adherence along with consequent microvascular thrombus when applied preventatively and to restore microvascular blood flood by disadhering leukocytes from the endothelium when applied postinjury. 41,42 As part of this study and reported elsewhere, 43 paired jugular venous and arterial samples were drawn on the first 202 randomized patients to measure transcerebral gradients of activated platelets and platelet-leukocyte conjugates. In that cohort, we observed a significant reduction in the transcerebral activation of platelet-monocyte conjugates after aortic cross-clamp release in patients who received lidocaine, which we hypothesized might reflect reduced cerebral inflammation during CPB.…”
Section: Perioperative Medicinementioning
confidence: 99%
“…Lidocaine has effects that depend on the total dose, and detrimental effects can be seen with elevated doses of lidocaine [27]. But lidocaine also has beneficial effects during surgery, providing (a) an anti-inflammatory effect; (b) an increase in the cardioprotective effect of cardioplegia; (c) a decrease in the risk of arrhythmias; and (d) a decrease in the risk of brain inflammation [15,16,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…This approach derived four factor scores that corresponded to four cognitive domains: verbal memory; abstraction and visuospatial orientation; visual memory; and attention and concentration. Postoperative cognitive dysfunction was de ned as a ≥ 1 standard deviation decrease of factor scores in one or more of these four cognitive domain from baseline to 6 weeks after surgery as previously described [6,35,36,[38][39][40][41][42][43].…”
Section: Cognitive Testingmentioning
confidence: 99%